Building an Identity on Paper: The Negotiation of Italianitá in the Early North American Ethnic Press - Franco Pierno (Diasporas: Circulations, Migrations, Histoire)
This article examines the language of one of the several Italian newspapers in-print between the end of the 19th century and beginning of the 20th century in North America, the Gazzetta del Massachusetts. The goal of this paper is to show how the journalistic activity borne by overseas immigrants have re-created and/or re-negotiated a new «Italianità» via a quite different use of the Italian language when compared to coeval papers printed in Italy.